Use the aquatic plant (Typha domingensis) as bioindicator to the accumulation of someheavy metals in Abu-Zariq Marsh Southern of Iraq - طالب فرهود آفاق (University of Thi-Qar Journal of Science, 2017)
The present study was conducted during the winter and summer of 2016 to study the bioaccumulation ofsome heavy metals and the use of (Typha domingensis )as bioindicator to the accumulation of these elementsthrough the food chain (water - sediments - aquatic plant) at three stations in Abu-Zariq Marsh - southern Iraq.Three heavy elements (Cd, Cu, Pb) were used in this study. The elements were studied in the dissolvedand particulate phases of water, sediment and aquatic plant (T. domingensis), the bioconcentration factor B C.F was calculated for the above studied elements in the aquatic plant tissue, which was as follows: (34867,26719 and 13333) once as concentrated in water respectivelyThe study concluded that the concentrations of the studied elements in the sediments are higher than in thewater with dissolved phase , particulate phase and aquatic plant , as follows: Sediments> aquatic plants (T.domingensis) > particulate part > Dissolves part of water . The abundance of elements is as follows: pb > Cu>Cd. In the water of its phases, sediments and aquatic plants, the concentration of metals are effects withchange in the seasons of the year, human activities and climatic factors is affected. This plant have a greatability to accumulate heavy elements and considered a good biological indicators for this type of pollutants.